HUBUNGAN KELEKATAN AYAH DENGAN KETERAMPILAN SOSIAL ANAK USIA 5–6 TAHUN DI KECAMATAN DUMAI TIMUR KOTA DUMAI - Angela, Maria; Chairilsyah, Daviq; Maria, Ilga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the relationship between father attachment and social skills of children aged 5–6 years in kindergarten schools in East Dumai District, Dumai City. This study used a quantitative correlational design. The sample consisted of 92 children aged 5–6 years and their fathers selected using saturated sampling techniques. Data were collected through questionnaires and observation sheets. Data analysis techniques included descriptive analysis, normality test, linearity test, and Pearson Product Moment correlation test with the assistance of IBM SPSS Statistics version 27. The results showed that father attachment was in the good category with a percentage of 77%, while children’s social skills were in the moderate category with a percentage of 61%. The hypothesis test results showed a correlation coefficient of 0.680 with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. These findings indicate a positive and significant relationship between father attachment and children’s social skills. It can be concluded that the better the father attachment, the better the social skills of children aged 5–6 years in East Dumai District, Dumai City.